Microbial Communities Present in Hydrothermal Sediments from Deception Island, Antarctica - Javier Vicente; Miguel de Celis; Alejandro Alonso; Domingo Marquina; Antonio Santos (Microorganisms, 2021)
Deception Island is a geothermal location in Antarctica that presents active fumaroles, which confers unique characteristics to this habitat. Several studies about microbial communities in Antarctica have been carried out, nevertheless, Antarctic microbiota is still partially unknown. Here we present a multidisciplinary study about sediments obtained by deposition during 4 years in which several approaches have been considered for their characterization. First, a physicochemical characterization, using ionic chromatography and mass spectrometry for the determination of most abundant ions (chloride and sulphate) and elements (mainly silicon), was conducted. In addition, the total microbial community was studied using a metataxonomical approach, revealing a bacterial community dominated by Proteobacteria and Thaumarchaeota as the main archaeal genera and a fungal community mainly composed by Aspergillaceae. Culture-dependent studies showed low microbial diversity, only achieving the isolation of Bacillus-related species, some of them thermophilic, and the isolation of common fungi of Aspergillus or Penicillium spp. Furthermore, diatoms were detected in the sediment and characterized attending to their morphological characteristics using scanning electron microscopy. The study reveals a high influence of the physicochemical conditions in the microbial populations and their distribution, offering valuable data on the interaction between the island and water microbiota.